2016
DOI: 10.4467/16890027ap.16.028.6097
|View full text |Cite
|
Sign up to set email alerts
|

New microsporidia, Glugea sardinellensis n sp (Microsporea, Glugeida) found in Sardinella aurita Valenciennes, 1847, collected off Tunisian coasts

Abstract: Abstract. Forty different sites, represented by 1483 samples, ranging from Alaska eastwards to Siberia, have been studied to assess the circumpolar testate amoebae species diversity. A total of 378 species have been recorded. The most common taxa are cosmopolitan and are widely distributed across various arctic habitats. Statistical analysis of testate amoebae species at sites across the Arctic have yielded geographic clusters of sampling sites that have been matched with climatic regions in the Arctic. We put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Regarding the molecular results from both phylogenetic trees with long and short sequences, the distribution of the Glugea species in the present study were identical to the ones observed in (Mansour et al 2016). Glugeathunni sp.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the molecular results from both phylogenetic trees with long and short sequences, the distribution of the Glugea species in the present study were identical to the ones observed in (Mansour et al 2016). Glugeathunni sp.…”
Section: Discussionsupporting
confidence: 86%
“…nov. could also infect clupeids as although the type host is T. thynnus, clupeids are frequent hosts of Glugea spp. (Mansour et al 2016) and, more importantly, the new species sequence is the same as KY882286 in Genbank, an unpublished sequence apparently wrongly identi ed as "G. plecoglossi" from Sardina pilchardus (Clupeidae). Therefore, an adequate management of the bait is highly recommendable.…”
Section: Discussionmentioning
confidence: 86%
“…Our results show that the number of parasites is related to sex, which is in agreement with the findings reported by Tantanasi et al (2012) and Ichalal et al (2015). This result corroborates those reported by Mansour et al (2016), who recorded high infection (P = 70.0%) with Glugea sardinellensis (11-13 cm) in small fish specimens. Host fish pick up Microsporidian parasites through the ingestion of free spores from the water column (Weissenberg 1968).…”
Section: Discussionsupporting
confidence: 93%
“…Host fish pick up Microsporidian parasites through the ingestion of free spores from the water column (Weissenberg 1968). Intestinal infection with microsporidia in S. aurita off the coast of Tunisia was first reported by Mansour et al (2016). A molecular study should be conducted in order to identify this Microsporidian to the species level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation